2016
DOI: 10.1186/s40169-016-0109-2
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative metabolomics profiling approach for the noninvasive assessment of liver histology in patients with chronic hepatitis C

Abstract: Background High-throughput technologies have the potential to identify non-invasive biomarkers of liver pathology and improve our understanding of basic mechanisms of liver injury and repair. A metabolite profiling approach was employed to determine associations between alterations in serum metabolites and liver histology in patients with chronic hepatitis C virus (HCV) infection. Methods Sera from 45 non-diabetic patients with chronic HCV were quantitatively analyzed u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
10
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 39 publications
4
10
0
1
Order By: Relevance
“…For HBV, the studies mostly sought biomarkers of the development of cirrhosis or HCC [ 24 , 46 , 47 , 48 , 49 ] or biomarkers simply of HBV infection itself [ 10 , 28 ]. Similar studies have been reported in the case of HCV for serum biomarkers of progression to HCC [ 21 , 22 , 23 ] and for hepatic fibrosis [ 17 , 19 ]. Since HCV infection can be treated, several reports deal with metabolomic changes before and after treatment that were interpreted as reflecting the metabolic effects of the virus [ 2 , 34 ].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…For HBV, the studies mostly sought biomarkers of the development of cirrhosis or HCC [ 24 , 46 , 47 , 48 , 49 ] or biomarkers simply of HBV infection itself [ 10 , 28 ]. Similar studies have been reported in the case of HCV for serum biomarkers of progression to HCC [ 21 , 22 , 23 ] and for hepatic fibrosis [ 17 , 19 ]. Since HCV infection can be treated, several reports deal with metabolomic changes before and after treatment that were interpreted as reflecting the metabolic effects of the virus [ 2 , 34 ].…”
Section: Discussionsupporting
confidence: 80%
“…Ex vivo metabolomics on urine and plasma obtained from HBV- and HCV- infected persons must rely on a more static metabolite picture rather than the dynamic metabolism of isotopomers. Although several investigators have reported metabolomic data on HBV and HCV patients, investigations were in general conducted to discover biomarkers for HBV [ 10 , 15 , 16 ] and HCV [ 15 , 17 , 18 , 19 ] cirrhosis or fibrosis, together with HCC metabolism with HBV [ 1 , 15 , 20 ] and HCV [ 3 , 15 , 21 ] infection or for progression to HCC [ 22 , 23 , 24 , 25 , 26 ]. Studies have also simply investigated the impact of HBV [ 27 , 28 , 29 , 30 ] or HCV [ 8 , 27 , 31 , 32 , 33 ] infection on the metabolome or the metabolic consequences of drug treatment [ 2 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…By using different methods to purify the metabolites' signature obtained from patients with ALD, we identified 5 serum and 1 urine metabolites, of which one (NLG) seemed accurate for identifying cirrhotic patients and another (DTEA) appeared to be more appropriate to select patients with severe disease. Multiple studies have analyzed the metabolomics profile for other hepatic diseases such as nonalcoholic fatty liver disease (NAFLD), viral hepatitis and hepatocellular carcinoma [24][25][26][27][28][29][30][31][32][33], trying to identify possible biomarkers for disease progression. In NAFLD, elevated hepatic concentrations of various lysophosphatidylcholine (LPC), lysophosphatidylethanolamine (LPE) and phosphatidylcholine (PC) species have been reported for human steatotic vs. nonsteatotic livers [24,30].…”
Section: Discussionmentioning
confidence: 99%
“…Three studies reported elevated bile salts in the liver [24] that spilled over to elevated bile acids in serum and plasma [25,26]. Regarding HCV infection, a metabolomic comparison of HCV-infected hepatocytes revealed small but significant increases in alanine, tyrosine and adenosine [27,30,32]. The metabolomic changes in hepatocellular carcinoma tend to point to increased fatty acid β-oxidation, with elevated acetate and 2-oxoglutarate (precursor of carnitine) and reduced free fatty acids, carnitine and carnitine esters [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Por isso, o número de amostras utilizados nos ensaios metabonômicos, em geral, é reduzido, quando comparado aos ensaios clínicos comumente encontrados na literatura. A Tabela 1 apresenta o número de amostras utilizadas nos trabalhos que fizeram uso da estratégia metabonômica (EMBADE et al, 2016;SARFARAZ et al, 2016;WEI et al, 2012)(GROMSKI et al, 2015).Vários estudos buscaram estabelecer um perfil metabólico como uma abordagem valiosa na caracterização de doenças e na identificação de biomarcadores do estado fisiológico e patológico dos indivíduos(BARTON et al, 2008).…”
unclassified